[Fish Processing Plant in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a fish processing plant in Heimaey. The tan and grey, rectangular building sits along the grey harbor water in the foreground surrounded by black lava rock. Eldfell is visible in the background, the dark mountain obscured by white clouds. A rusted, white ship is visible along the left edge of the photograph.